Kontribusi Terapi Brain Gym terhadap Fungsi Kognitif Pasien Skizofrenia - Athallah, Jihan Fairuz Thifal; Untari, Rita (Jurnal Terapi Wicara dan Bahasa, 2025)
Background: Schizophrenia is a psychiatric disorder that affects human brain function, normal cognitive and emotional functions and human behavior. This decrease in cognitive function has an impact on occupational, social and economic functional activities. Improving cognitive function in people with schizophrenia requires an action, treatment, and therapy such as cognitive remediation. One way is with brain gym. Brain-Gym is a method of training the brain through simple movements that serve to improve a person's cognitive abilities in terms of concentration, memory, observation, creativity and problem solving. Objectives: The purpose of this study was to determine the contribution of brain gym therapy on cognitive function of schizophrenia patients at RSJ Grhasia Yogyakarta. Methods: Quantitative research pre- experimental design  one group pre-test and post-test. This research was conducted with a sample of 25 people (19-59 years). The instrument used in this research is the Schizophrenia Cognition Rating Scale (SCorS).  Results: the results of the hypothesis were obtained with a sig value of 0.000 (p value <0.05), which means that there is a significant difference between the pre-test and post-test results.  Brain gym is proven to have an effect on the cognitive function of schizophrenia patients at RSJ Grhasia Yogyakarta. Conclusion: Providing brain gym therapy has proven to be effective in influencing the cognitive function of schizophrenia patients at RSJ Grhasia Yogyakarta.  Brain gym therapy  can be a recommendation for cognitive remediation therapy for schizophrenia patients so that their cognitive abilities can function optimally. Keywords: Brain Gym, Cognitive, Schizophrenia